2019
DOI: 10.1620/tjem.249.291
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the Types of Treated Cancer between Clinics and Small-to-Middle-Sized Hospitals in Rural Communities of Japan

Abstract: Resolution of regional disparities in cancer mortality is global challenge. Establishing an equal system of cancer treatment throughout the country is required under the Cancer Control Act in Japan. The types of treated cancer may reflect practical experience at the institutions and cooperation to other institutions. This study investigated the types treated at the institutions in rural communities of Japan. A questionnaire survey was conducted for 811 public rural institutions (clinics and small-to-middle-siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Cancer patients were more likely to visit higher-level institutions compared to those with adenoma, which seems plausible considering that multidisciplinary approach and specialized experience is crucial for the management of cancer. Previous studies have shown similar findings that patients with cancer were more inclined to visit hospitals than clinics to seek out cancer specialists 23 , 24 . Patients visiting higher-level institutions were also older.…”
Section: Discussionsupporting
confidence: 53%
“…Cancer patients were more likely to visit higher-level institutions compared to those with adenoma, which seems plausible considering that multidisciplinary approach and specialized experience is crucial for the management of cancer. Previous studies have shown similar findings that patients with cancer were more inclined to visit hospitals than clinics to seek out cancer specialists 23 , 24 . Patients visiting higher-level institutions were also older.…”
Section: Discussionsupporting
confidence: 53%
“…Some responding physicians expected clinic-based GPs to be involved in chemotherapy; in actuality, clinic-based GPs may also help patients with prostate and breast cancers through hormonal therapies [ 30 ]. Although clinic-based GPs did not intend to get involved in ‘the management of adverse effects of chemotherapy’ as a priority, with regard to irAEs, it is important to note that new cancer immunotherapies may produce new adverse events in the form of various types of symptoms and diseases [ 31 ].…”
Section: Discussionmentioning
confidence: 99%